Neuropsychophysiological Basis of Communicative Influence - Kutuza, Natalia; Varynska, Alla (Journal of History Culture and Art Research, 2020)
The article is devoted to the communicative influence, which has a complex nature, due to the indivisible unity of the neurophysiological, psychological and linguistic components in its architectonics. The main attention is paid to the neuropsychophysiological basis of influence, where it is accented in particular on emotions as a "blocker" of critical perception of information. It is emphasized that with the help of neuropsychophysiological processes it is possible to explain the effect of influence on the conscious and subconscious levels, the specific functioning of the hemispheres, where the effect is associated with subconscious processes and directed to the right (subdominant) hemisphere. The role of consciousness, which is almost always associated with volitional control, control of one’s own psyche and behavior, as well as speech, is pointed out in the work, that is, the control function is put forward, the rational side of the person is actualized. The subconsciousness is characterized by uncontrollability, irrationality, and often "inactivated" when physiologically impossible to rationally process an array of information. It has been discovered that information subjected to subconsciousness under certain conditions is actualized and affects speech and behavioral reactions of a person, as actively used by suggestors, since the human brain can be programmed for certain actions, since the vast majority of human activity controls the subconscious. Significant role in influencing the function of the cerebral hemispheres, whose structure consists of the left and right hemispheres, which, when processing the information in the process of cognitive activity perform various cognitive operations, but in the implementation of any mental function involved the entire brain entirely. The left hemisphere controls straightforward, logical linguistic thinking, forming a model that is easy to analyze; rights control non-verbal thinking, visual, spatial information, so-called "figurative thinking". Actually, emotions are controlled by the right (subdominant) hemisphere, on which the suggestion is oriented, establishing contact with the psychophysiological reserves of the recipient. In the course of the study, it has been proved that in order to find out the deep foundations of communicative influence, a neuropsychophysiological component must be involved in general, which explains the specifics of conscious and subconscious processes of perception, speech comprehension, and the functioning of the cerebral hemispheres. The leading role in suggestive influence is given to the subconscious level, since the holistic sense of the message is perceived gestaltly. The left hemisphere processes information at the level of consciousness, rationally, right - at the subconscious level, actualizes the emotional processes, which constitute the basis of suggestive influence.